Switzerland : Financial Sector Assessment Program; Technical Note; An Assessment of Insurance Core Principles for the Reinsurance Industry. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2007)
This technical note discusses key findings of the assessment of Insurance Core Principles (ICP) for the reinsurance industry for Switzerland. It reveals that the Swiss reinsurance market is dominated by three large players with a strong international presence. The reinsurance industry comprises 20 professional reinsurers and 50 reinsurance captives with gross premiums written totaling SwF 37.4 billion for 2005. Swiss Re, European Re, and Converium have consistently maintained more than 75 percent market share. More than 95 percent of reinsurance premiums came from foreign business.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet